2019
DOI: 10.1002/aelm.201800707
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Electrical Performances of In2O3 Nanofiber Channel Thin Film Transistors via Sr Doping

Abstract: Although In2O3 nanofibers (NFs) are considered as one of the fundamental building blocks for future electronics, the further development of these NFs devices is still seriously hindered by the large leakage current, low on/off current ratio (Ion/Ioff), and large negative threshold voltage (VTH) due to the excess carriers existed in the NFs. A simple one‐step electrospinning process is employed here to effectively control the carrier concentration of In2O3 NFs by selectively doping strontium (Sr) element to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In the meantime, Sr-doped and Fe-doped hollow In 2 O 3 microspheres reported by Shen et al showed a response of 9.4 and 5.5–100 ppm formaldehyde . Up to now, many techniques have been put forward to synthesize the one-dimensional In 2 O 3 nanostructures, such as chemical vapor deposition, , template-assisted approach, and electrospinning, etc. There are usually two crystal structures for In 2 O 3 , i.e., body-centered cubic (bcc) (c-, Ia 3, a = 10.118 Å) and rhombohedral (rh - , R 3 j c , a = 5.478 Å and c = 14.51 Å) .…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, Sr-doped and Fe-doped hollow In 2 O 3 microspheres reported by Shen et al showed a response of 9.4 and 5.5–100 ppm formaldehyde . Up to now, many techniques have been put forward to synthesize the one-dimensional In 2 O 3 nanostructures, such as chemical vapor deposition, , template-assisted approach, and electrospinning, etc. There are usually two crystal structures for In 2 O 3 , i.e., body-centered cubic (bcc) (c-, Ia 3, a = 10.118 Å) and rhombohedral (rh - , R 3 j c , a = 5.478 Å and c = 14.51 Å) .…”
Section: Introductionmentioning
confidence: 99%
“…Among circuit components, inverters are widely considered to be the basic component that can be manufactured based on E‐mode devices. [ 24 ] In this work, based on the InLaO‐0.5 TFT, an inverter for logic circuits has been built with an external 3 MΩ resistor, exploring the potential application of the InLaO‐0.5 TFT in logic circuits. The circuit schematic of the resistor‐loaded inverter is shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…Transparent metal-oxide (MO) thin films have been extensively explored as fundamental building blocks for the next generation of electronic and optic devices due to their outstanding electrical performance, high optical transparency and environmental stability. [1][2][3][4][5][6] Various deposition techniques have been developed to prepare high-quality MO films. The market is currently dominated by vacuum-based techniques (physical vapor deposition and chemical vapor deposition), [7][8] followed by chemical-solution-deposition (CSD)-based deposition techniques, such as spray, 1 spin or dip coating [9][10][11] and inkjet printing [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%